Effects of saline contents on tensile behavior and fiber-matrix interaction in seawater sea-sand engineered cementitious composite (SS-ECC) - Gao, Xiumei; Li, Weiwen; Ke, Linyuwen; Wang, Peng; Wei, Jiaying; Zhong, Ying; Wu, Haoliang; Zhou, Yingwu (Construction & building materials, 2025)
Seawater sea-sand engineered cementitious composite (SS-ECC) demonstrates effectiveness in crack control and resource utilization, enabling it as a promising construction material for marine infrastructure. However, the variable tensile performance of SS-ECC with different mix designs imposes a great challenge to practical implementation. To address this issue, a comprehensive investigation is conducted in this study to bridge the gap between macroscopic tensile properties and microscopic fiber-cement interactions in SS-ECC. Firstly, both normal- and high-strength ECC are fabricated incorporating polyvinyl alcohol (PVA) and polyethylene (PE) fibers. Subsequently, the intrinsic stress-strain characteristics and crack patterns are scrutinized through uniaxial tensile testing of dogbone specimens. Additionally, bond strength and fracture energy at the fiber-cement interface are assessed via pullout tests. Furthermore, heat release is quantified to delineate the cement hydration process, together with X-ray diffraction (XRD) analysis identifying cement hydration products and scanning electron microscopy (SEM) capturing surface micromorphology of tested fibers. Research findings reveal that saline contents from seawater and sea sand lead to a 1.25 % (0 %) and 10.26 % (21.21 %) decrease in ultimate stress and strain for high (normal)-strength ECC, respectively. This reduction is attributed to enhanced bond strength (by 24.9 %) and fracture energy (by 79.4 %) at the fiber-cement interface, along with accelerated cement hydration influenced by the presence of saline contents. These results establish connections between the tensile properties of SS-ECC and its microstructural attributes, offering engineers profound insights into load transfer mechanisms within SS-ECC and enhancing its applicability in marine construction projects. •The relationship between macroscopic tensile properties and microscopic fiber-cement interactions has been established.•Saline content results in 1.2 % (0 %) and 10.3 % (21.2 %) drop in ultimate stress and strain for high (normal) -strength ECC.•Saline contents enhance bond strength (24.9 %) and chemical debonding energy (79.4 %) at fiber-cement matrix interface.•Improvement in fiber-cement matrix interaction is attributed to accelerated cement hydration facilitated by saline contents.